Editing Continuity in Documentary Program “Kultur Nusantara: Panghulu Niniak Mamak” - Achmad Iqbal Ashrye; Marwiyati Marwiyati (Jurnal Imiah Teknik Studio, 2022)
The importance of image continuity, among others, is to create an attractive program so that the message can be conveyed clearly, but sometimes it is often overlooked in an audio-visual production. This is the underlying reason of this television documentary program making, to apply the continuity of each image by applying transition technique, so that it could give emphasis on the displayed image to become a quality show and be convenient to watch. Editing continuity can be achieved by giving attention to the harmony between image and sound by combining several editing techniques including cutting by narration, cutting by moment, color correction, as well as motion graphics. The cutting by narration technique is a cutting technique that aligns the image with the narration, while the cutting by moment technique is intended to create image changes according to the moment of the program production, and color correction is to align image colors so that color jumping does not occur. With the implementation of this method, the images, sounds, and colors become balanced and harmonious so that the information conveyed will be clearer, more interesting and informative.